Cost Impact of the Federal Coal Mine Health and Safety Act of 1969 (TRANSACTIONS - VOL. 256) - James E. Breland (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1975)
A case study of tangible and intangible costs incurred by a coal mining company for meeting the requirements of the Federal Coal Mine Health and Safety Act of 1969 is discussed. For clarity, the data is presented on a "before and after" basis, with special emphasis on safety records, costs, and production performance. The cost figures have been subjected to outside verification.